Pathological features of lymph node metastasis for predicting biochemical recurrence after radical prostatectomy for prostate cancer - Carlsson, Sigrid V; Tafe, Laura J; Chade, Daher C; Sjoberg, Daniel D; Passoni, Niccolo; Shariat, Shahrokh F; Eastham, James; Scardino, Peter T; Fine, Samson W; Touijer, Karim A (The Journal of urology, 2013)
Subclassification of nodal stage may have prognostic value in men with lymph node metastasis at radical prostatectomy. We explored the role of extranodal extension, size of the largest metastatic lymph node and the largest metastasis, and lymph node density as predictors of biochemical recurrence. We reviewed pathological material from 261 patients with node positive prostate cancer. We examined the predictive value when adding the additional pathology findings to a base model including extraprostatic extension, seminal vesicle invasion, radical prostatectomy Gleason score, prostate specific antigen and number of positive lymph nodes using the Cox proportional hazards regression and Harrell concordance index. The median number of lymph nodes removed was 14 (IQR 9, 20) and the median number of positive lymph nodes was 1 (IQR 1, 2). At a median followup of 4.6 years (IQR 3.2, 6.0) 155 of 261 patients experienced biochemical recurrence. The mean 5-year biochemical recurrence-free survival rate was 39% (95% CI 33-46). Median diameter of the largest metastatic lymph node was 9 mm (IQR 5, 16). On Cox regression radical prostatectomy specimen Gleason score (greater than 7 vs 7 or less), number of positive lymph nodes (3 or greater vs 1 or 2), seminal vesicle invasion and prostate specific antigen were associated with significantly increased risks of biochemical recurrence. On subset analysis metastasis size significantly improved model discrimination (base model Harrell concordance index 0.700 vs 0.655, p = 0.032). Our study confirms that the number of positive lymph nodes is a predictor of biochemical recurrence in men with node positive disease. The improvement in prognostic value of measuring the metastatic focus warrants further investigation.